FOLLOW THE LEADER. Issue 4 (December 2013) - Anderson, Jamie; Reckhenrich, Jörg; Kupp, Martin
<x xml:space="preserve">Abstract</x> Social media platforms, such as Facebook and Twitter, provide leaders with a remarkable new toolset to engage with followers, but they must be used wisely for maximum impact. Jamie Anderson, Jörg Reckhenrich and Martin Kupp explore the evolving art of followership